2021
DOI: 10.1007/s13311-021-01023-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging, Urinary, and Plasma Biomarkers of Treatment Response in Huntington's Disease: Preclinical Evidence with the p75NTR Ligand LM11A-31

Abstract: Huntington’s disease (HD) is caused by an expansion of the CAG repeat in the huntingtin gene leading to preferential neurodegeneration of the striatum. Disease-modifying treatments are not yet available to HD patients and their development would be facilitated by translatable pharmacodynamic biomarkers. Multi-modal magnetic resonance imaging (MRI) and plasma cytokines have been suggested as disease onset/progression biomarkers, but their ability to detect treatment efficacy is understudied. This study used the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 135 publications
(265 reference statements)
0
11
0
Order By: Relevance
“…The follow-up of the BEL-AGE cohort in the next years will hopefully help to answer this open question. In addition to the possibility of p75 NTR as an early diagnostic biomarker, its role could be extended to disease progression ( Shepheard et al, 2017 ), and also be of interest as a pharmacodynamic biomarker to assess the effect of treatment, which is lacking in multiple neurological and psychiatric diseases ( Simmons et al, 2021 ). These latter possibilities have been extensively discussed by Shepheard et al (2017) and Simmons et al (2021) and were also discussed in a recent meta-analysis by Shi et al (2021) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The follow-up of the BEL-AGE cohort in the next years will hopefully help to answer this open question. In addition to the possibility of p75 NTR as an early diagnostic biomarker, its role could be extended to disease progression ( Shepheard et al, 2017 ), and also be of interest as a pharmacodynamic biomarker to assess the effect of treatment, which is lacking in multiple neurological and psychiatric diseases ( Simmons et al, 2021 ). These latter possibilities have been extensively discussed by Shepheard et al (2017) and Simmons et al (2021) and were also discussed in a recent meta-analysis by Shi et al (2021) .…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified high p75 NTR levels in 15% of the BEL-AGE individuals. The p75 NTR receptor is recently being proposed as a diagnostic biomarker of Alzheimer's disease in serum (Jiao et al, 2015), and was also proposed as a prognostic, disease progression and potential pharmacodynamic biomarker for ALS and Huntington's disease in urine, with increase in p75 NTR ECD happening prior to symptoms appearance in ALS (Shepheard et al, 2014(Shepheard et al, , 2017Shi et al, 2021;Simmons et al, 2021). Whether this predictive pattern is specific to these diseases remains unknown.…”
Section: P75 Ntr Extracellular Domain As a Biomarkermentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, because of the leakage of CNS molecules through the BBB, blood represents a reliable source of several biomarkers, such as NfL [ 27 ]. Other biofluids have been tested, such as urine , from which Simmons et al, 2021 [ 37 ] could detect higher p75NTR in HD mice compared to controls. Saliva was demonstrated to contain detectable levels of tHTT, correlating with some HD clinical measures [ 38 ] and feces was used to detect bacterial alterations related to clinical features [ 39 ].…”
Section: Current Biomarkers In Huntington’s Diseasementioning
confidence: 99%
“…In search of other sources of accessible biofluids, several studies started to explore the presence of possible biomarkers in the urine of R6/2 HD mouse models. Indeed, the levels of p75 NTR were increased in R6/2 mice compared to WT mice urinary levels [ 37 ]. p75 NTR was already shown to play a role in memory dysfunction in HD patients [ 43 ] and to be altered in HD patients’ striatum [ 44 ].…”
Section: Current Biomarkers In Huntington’s Diseasementioning
confidence: 99%